In the service of a higher good : Resilience of academics under managerial control - Jaakko Siltaloppi; Juha Laurila; Karlos Artto (Sage, 2022)
This article extends the literature of resistance in organisational settings by examining the
forms and sources of resistance that endure even in the face of successive adversities. This
article characterises such resistance as resilience and elaborates on this concept empirically
in the university context by showing how academics find new ways to maintain and promote
their professional agendas despite successive, unpredictable managerial interventions typical of
the contemporary university. In our analysis, we identify three forms of resilience – protective,
independent, and adaptive – each of which draws on specific professional values that we term
constitutive goods. The focus on constitutive goods highlights the moral grounding of resistance
that comes into play, especially in situations in which the actors have something fundamentally
valuable at stake, and which they feel compelled to defend. Moreover, resilience extends the
focus beyond situated resistance tactics to a process geared towards protecting constitutive
goods against control over the long term.